2023
DOI: 10.3390/pharmaceutics15020328
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Salivary Caffeine Kinetics of 13C and 12C Caffeine for Gastric Emptying of 50 mL Water

Abstract: Gastric water emptying as a critical parameter for oral drug absorption can be investigated by several imaging techniques or by the interpretation of pharmacokinetics of appropriate substances. Recently introduced salivary caffeine kinetics is a valuable tool, but the required caffeine abstinence limits its applicability. To avoid the caffeine abstinence, stable isotope-labeled caffeine might be used, but the representability and transferability of kinetics for evaluation of gastric emptying must be demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In recent years, some studies dealing with GI fluid dynamics have not adequately distinguished real fluid movement from apparent fluid movement. The effect of gastric emptying of ingested water and gastric fluid on drug absorption was reported by Grimm et al, while many aspects of intestinal fluid dynamics remain unclear 31 , 32 . In the present study, we analyzed GI fluid dynamics quantitatively from both perspectives (apparent and real) using FD-4 and [ 3 H]water.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, some studies dealing with GI fluid dynamics have not adequately distinguished real fluid movement from apparent fluid movement. The effect of gastric emptying of ingested water and gastric fluid on drug absorption was reported by Grimm et al, while many aspects of intestinal fluid dynamics remain unclear 31 , 32 . In the present study, we analyzed GI fluid dynamics quantitatively from both perspectives (apparent and real) using FD-4 and [ 3 H]water.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in previous studies with the application of the salivary tracer technique, about 25-35 mg of caffeine were used [13,19,20]. Moreover, a recent study showed no influence of this caffeine labelling on gastric emptying by comparison of MRI data sets [20]. Black iron oxide was used to distinguish the core (black powder) from the coating (white powder) during manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of 25 mg of caffeine used for the determination of gastric emptying is already below the usual dose of caffeine in caffeinated beverages, and thus should not raise concerns about its safety [30] or its pharmacological effect [31,32]. Similarly, in previous studies with the application of the salivary tracer technique, about 25-35 mg of caffeine were used [13,19,20]. Moreover, a recent study showed no influence of this caffeine labelling on gastric emptying by comparison of MRI data sets [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations